2022
DOI: 10.1186/s13063-022-06406-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of kinesiophobia on pain intensity, disability, muscle endurance, and position sense in patients with chronic low back pain—a case-control study

Abstract: Background Patients with chronic low back pain (CLBP) frequently present with kinesiophobia. Though large body of evidence reported the impact of kinesiophobia in patients with CLBP, there are paucity of studies in associating kinesiophobia to muscle endurance and position sense in patients with CLBP. The primary aim of the study is to compare the impact of kinesiophobia on lumbar extensor endurance, position sense in patient with CLBP, and asymptomatic individuals. Secondarily, we aim to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…Limited studies have evaluated the impact of kinesiophobia on LJPS in CLBP individuals. Similar to our study methods, Kandakurti et al [ 26 ] assessed the impact of kinesiophobia on lumbar extensor endurance and position sense in patients with CLBP, and this study showed that individuals with increased TSK scores had decreased lumbar extensor endurance and high LJPS.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Limited studies have evaluated the impact of kinesiophobia on LJPS in CLBP individuals. Similar to our study methods, Kandakurti et al [ 26 ] assessed the impact of kinesiophobia on lumbar extensor endurance and position sense in patients with CLBP, and this study showed that individuals with increased TSK scores had decreased lumbar extensor endurance and high LJPS.…”
Section: Discussionsupporting
confidence: 64%
“…LJPS is estimated based on the ability of an individual to actively reposition the lumbar spine to a target position, and this reposition accuracy is measured in degrees [ 22 , 23 ]. Previous studies have shown a strong relationship between LJPS, kinesiophobia, pain intensity, and functional disability [ 24 , 25 , 26 ]. However, the evidence regarding how kinesiophobia impacts LJPS in CLBP is limited and has yet to be explored.…”
Section: Introductionmentioning
confidence: 99%